FORMULATION AND EVALUATION OF LIQUID ORAL SUSPENSION OF PARACETAMOL USING NEWLY ISOLATED AND CHARACTERIZED HYGROPHILA SPINOSA SEED MUCILAGE AS SUSPENDING AGENT - Krishna, Anjali; Mohanan, Shan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study was to demonstrate and evaluate the suspending property of newly isolated, purified, and characterized Hygrophila spinosa seed mucilage in liquid oral suspensions of paracetamol. Methods: Isolation of mucilage from H. spinosa seeds was done by maceration process, and then it was characterized by phytochemical screening, solubility, pH, swelling index, flow rate, viscosity, loss on drying, and cytotoxicity. The characterized mucilage was then used as a suspending agent for the preparation of suspensions containing paracetamol as a model drug. The prepared formulations were then evaluated for different parameters such as sedimentation volume, redispersibility, flow rate, pH, viscosity, and other physical examination. Results: The isolated mucilage is a polysaccharide with no impurities and nontoxic in nature. It has got enough swellability and good viscosity. The prepared suspensions were evaluated, and the results such as sedimentation volume, redispersibility, flow rate, pH, viscosity, and other physical examination showed its suspending property. Conclusion: The study revealed that a lesser amount of H. spinosa seed mucilage can produce a good suspension. By this study, it could be find out that a 1/5th quantity of mucilage (0.2%) is only required to prepare a suspension of paracetamol when compared with suspensions prepared of compound tragacanth (1%) and sodium carboxymethyl cellulose (1%) as suspending agents. Thus, by this study, it can be stated that the mucilage from H. spinosa possesses all the criteria needed by a standard suspending agent. Â 